Design and Implementation of a Quantitative Risk Assessment Model for UK Road Tunnels (Global Journal of Science Frontier Research, 2023)
One of the critical transportation infrastructures is road tunnels and fire safety is one of the important aspects of their operation. Interaction between the fire, tunnel users, traffic, and fire safety measures influences fires in road tunnels. Therefore, a complex model is required to analyse the risk and quantify the consequences. In this paper, a novel quantitative risk analysis model developed for UK road tunnels is presented consisting of a quantitative consequence analysis model and a quantitative frequency frequency analysis model. The proposed quantitative consequence analysis model is provided through three sub-models; queue model, distribution model, and egress model. The frequency analysis is via an event tree that takes into account the tunnel fire rate in UK road tunnels. After a brief description of this model, the proposed method is illustrated through a case study of an urban road tunnel. The effect of different emergency ventilation systems on societal risk and sensitivity of the model to premovement time, accident frequencies involving Heavy Good Vehicles (HGVs), tenability threshold temperature, and different burning vehicles were studied in this case study.
Keywords: fire safety; quantitative risk analysis; consequence analysis; frequency analysis